Salvage cryotherapy in patients undergoing endoscopic eradication therapy for complicated Barrett’s esophagus - Spiceland, Clayton M.; Elmunzer, B. Joseph; Paros, Samuel; Roof, Logan; McVey, Molly; Hawes, Robert; Hoffman, Brenda J.; Elias, Puja S. (Endoscopy International Open, 2019)
Background and study aims Some patients with dysplastic Barrett’s esophagus (BE) experience suboptimal response to radiofrequency ablation (RFA), endoscopic mucosal resection (EMR), or the combination. Cryotherapy has been used as salvage therapy in these patients, but outcomes data are limited. We aimed to assess clinical outcomes among a large cohort of patients with dysplastic BE whose condition had failed to respond to RFA and/or EMR.Patients and methods This was a retrospective cohort study of consecutive cases of dysplastic BE or intramucosal carcinoma (IMC) treated with salvage cryotherapy at a tertiary-care academic medical center. The primary goal of cryotherapy treatment was eradication of all neoplasia. The secondary goal was eradication of all intestinal metaplasia. The proportion of patients undergoing salvage cryotherapy who achieved complete eradication of dysplasia (CE-D) and metaplasia (CE-IM), as well as the time to CE-D and CE-IM were calculated.Results Over a 12-year period, 46 patients received salvage cryotherapy. All patients underwent RFA prior to cryotherapy, either at our center or prior to referral, and 50 % of patients underwent EMR. A majority of patients (54 %) had high-grade dysplasia (HGD) at referral, while 33 % had low-grade dysplasia (LGD), and 13 % had IMC. Overall, 38 patients (83 %) reached CE-D and 21 (46 %) reached CE-IM. Median time to CE-D was 18 months, median number of total interventions (RFA, cryotherapy, and EMR) was five, and median number of cryotherapy sessions was two.Conclusion Salvage cryotherapy appears safe and effective for treating BE that is refractory to RFA and/or EMR.